2016
DOI: 10.1111/ajo.12530
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a multidisciplinary obstetric emergency team training program, the In Time course, on diagnosis to delivery interval following umbilical cord prolapse – A retrospective cohort study

Abstract: Obstetric emergency training was associated with improved teamwork, as evidenced by the improved documentation post-training in this study, but not with improved diagnosis to delivery interval. Long-term follow-up studies are required to ascertain whether training has an impact on longer-term paediatric outcomes, such as cerebral palsy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The change in documented manoeuvres may simply reflect an improvement in documentation in the post‐training era. As has been previously noted, improvements in documentation are likely to demonstrate improved teamwork and communication, and are additionally likely to result in improvements in medico‐legal outcomes . As our health authority does not currently link insurance payments to demonstrated improvements in documentation, this benefit remains under‐recognised.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The change in documented manoeuvres may simply reflect an improvement in documentation in the post‐training era. As has been previously noted, improvements in documentation are likely to demonstrate improved teamwork and communication, and are additionally likely to result in improvements in medico‐legal outcomes . As our health authority does not currently link insurance payments to demonstrated improvements in documentation, this benefit remains under‐recognised.…”
Section: Discussionmentioning
confidence: 98%
“…The In Time course is a one‐day case‐based simulation training course focused on obstetric emergencies. It is designed to improve multi‐disciplinary teamwork . There is a strong emphasis on situational awareness, communication, knowledge, practical skills and manoeuvres in the context of managing obstetric emergencies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, such high perinatal mortality rates may be related to a prolonged period of fetal hypoxia before the patients were transferred to the hospitals for decision of delivery, and hence their result may not be applicable to developed countries. 1,4,7 Faiz et al demonstrated a contradictory result of improved Apgar score at 5 minutes when decision-to-delivery interval was longer than 20 minutes. 16 This paradoxical phenomenon was also demonstrated in Group 2, and likely resulted from a selection bias, in which the severe cases with poorer outcome were delivered urgently, whereas mild cases with good outcome tended to be delivered less urgently.…”
Section: Discussionmentioning
confidence: 99%
“… 31 However, Copson et al found non-significant improvements in all aspects of management apart from an increase in the number of babies with Apgar scores <7 at 5 minutes, and explained this by the high standard care prior to training. 32 In their case, Copson et al concluded that simulation training would maintain the high standard of care in their units.…”
Section: Simulation Training For Umbilical Cord Prolapsementioning
confidence: 99%